Self-Confidence and Cognitive Speed: Key Predictors of Topspin Accuracy in Competitive Table Tennis - Jeki Haryanto; Clemens Drenowatz; Jon Mikel Picabea; Padli; Fiky Zarya; Yovhandra Ockta; Vlad Adrian Geantă (OVS LLC, 2024)
Background. Table tennis players often use topspin shots in order to score. For many athletes, this stroke is crucial to winning, making it a favorite among players. It is more probable that accurate topspin strokes will make it harder for opponents to return the ball. As a result, players who can maintain topspin stroke accuracy over time are more likely to win matches. Objectives. This study aimed to examine the association between self-confidence (SC) and cognitive processing speed (CPS) with topspin accuracy (TPA) in table tennis. Materials and methods. This study used a correlation method with a quantitative approach. A total of 82 participants (aged: 20.0 ± 0.6 years) were involved in this study. Data on topspin accuracy was collected by administering a topspin accuracy test, followed by administering a self-confidence questionnaire and cognitive processing speed test. Pearson correlation and linear regression analysis were used to determine the association between the variables. Results. The findings of this study show (1) a positive relationship between self-confidence and topspin accuracy (r = 0. 430, p < 0.05); (2) a positive relationship between cognitive processing speed and topspin accuracy (r = 0.374, p < 0.05). Conclusions. Topspin accuracy is influenced by cognitive processing speed and self-confidence. Therefore, in order to improve table tennis topspin performance, coaches should take these factors into account. The results of this study can have a significant impact on training programs, where mental skills training, such as boosting self-confidence and enhancing cognitive processing speed, should be integrated into technical and tactical training routines. This approach will allow athletes to not only refine their physical skills but also strengthen their psychological resilience, ultimately leading to better performance in competitive matches.